Świat bez dydaktyki, pracownicy naukowi jako publikacje, studenci jako efekty kształcenia - Ilnicki, Rafał (Człowiek i Społeczeństwo, 2020)
The article presents a grim vision of the world in which teaching is no longer conducted. This serves as a basis for a critical evaluation of the abolishment of didactic process in favor of publications. The main idea is that the basis for the teaching process in the humanities is the only way in which humanities can develop understanding that will reach culture through the mediation of students which are the beneficiaries of humanistic ideals of teaching. There are also presented ideas concerning possible practices that counter negative tendencies. One of them is focused on creating publications about the humanistic didactic process that would include students not only as forces to gain knowledge withing the university but also as an active participants of culture that can develop themselves through the humanistic ideals. Special role of cultural studies in this process is also emphasized.